FREQUENCY OF CONGENITAL HEARING LOSS IN NEONATES - Ahmed, Shakeel; Sheraz, Shahida; Malik, Sohail Ahmad; Ahmed, Nasir Rafiq; Farooq, Shahid; Raheem, Abdul; Basheer, Faisal; Nayyar, Zameer Ahmad; Malik, Fazal -e- (Journal of Ayub Medical College Abbottabad, 2018)
Background: Congenital deafness is commonest birth defect and it affects 2-4 neonates among 1000 live births. Detection and intervention specially before 6 months of age prevents severe linguistic, educational and psychosocial repercussions and helps the deaf child in the development of normal speech and language. Children who are identified after 6 months of age experience great difficulties in attaining speech and language. Methods: To find out the frequency of hearing loss in neonates, a hospital based observational study was conducted in Combined Military Hospital Abbottabad from June-to December 2014. One thousand new-borns selected by consecutive sampling within a specified period of time were subjected to Otoacoustic Emission (OAE) testing. Brain Evoked Response Audiometry (BERA) evaluation was performed in all those who failed OAE testing to confirm the hearing loss. Children born with microtia, meatal stenosis, cleft palate, craniofacial abnormalities and syndromic illnesses were excluded from the study. Results: Of 1000 new-borns screened, 465 were males and 535 were females whereas 632 (63.2%) were delivered through C-section and 368 (36.8%) were born via SVD. Four hundred and ninety-one (49%) babies had a positive history of consanguinity among the parents. Out of 1000 infants 13 were having hearing loss which was later on confirmed on BERA evaluation. Among them 7 were males and 6 females, 9 (69%) were born through SVD and 4 (31%) through C-section and 8 (61.5%) new-borns had a positive history of consanguinity among their parents. In all these 13 patients only 2 (15%) patients had profound while the remaining 11 (85%) had moderate to severe hearing loss. Conclusion: Frequency of hearing loss in neonates is much higher in our study (13 per 1000) as compared to other parts of the world and demands that more studies should be undertaken on this subject to confirm this. Keywords: Neonatal screening for hearing loss; Congenital deafness; Hearing loss in neonates; Otoacoustic Emission Scan.